Agency without actors?
1 online resource (240 pages)
Keywords: "Agency without Actors? New Approaches to collective Action is rethinking a key issue in social theory and research: the question of agency. The history of sociological thought is deeply intertwined with the discourse of human agency as an effect of social relations. In most recent discussions the role of non-humans gains a substantial impact. Consequently the book asks: Are nonhumans active, do they have agency? And if so: how and in what different ways? The volume offers a critical state-of-the-art debate of internationally and nationally leading scholars within Sociology, Social Anthropology and STS on agency (Latour, Law, Michael, Rammert etc.). It fosters the productive exchange of empirical settings and theoretical views by outlining a wide range of novel accounts that link human and non-human agency. It tries to understand social-technical, political and environmental networks as different forms of agency that produce discrete and identifiable entities like humans, animals, technical artifacts. It also asks how different types of (often conflicting) agency and agents actors are distinguished in practice, how they are maintained and how they interfere with each other"--